2011
DOI: 10.4103/0971-6866.82186
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of smoking genotoxicity in Turkish young adults

Abstract: BACKGROUND:For the past few decades, it has been widely known in developed countries that tobacco is dangerous, but it is still insufficiently realized how big these dangers really are.AIMS:To determine and evaluate micronuclei (MN) frequencies of young smokers and nonsmokers in three different tissues (peripheric blood lymphoctes, buccal mucosa, and exfoliative urothelial cells) at the same time.MATERIALS AND METHODS:MN assay was performed on buccal mucosa, urothelial cells, and peripheric blood lymphocyte sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…In this context, the detection of increased levels of MN in urothelial cells can be a useful approach to detect individuals prone to have bladder cancer, and/or to assess the prognosis of the pathology. Increased MN frequencies in urothelial cells of humans populations have been associated to those risk factors involved in bladder cancer such as tobacco (Zamani et al, ), arsenic (Paul et al, ), and occupational exposure to organic solvents (Hoyos‐Giraldo et al, ). Additionally, MN formation was detected in the bladder cells of rats exposed to orto‐phenylphenol, a fungicide and antibacterial agent well known as a bladder tumor inducer in rats (Balakrishnan and Eastmod, ).…”
Section: Discussionmentioning
confidence: 99%
“…In this context, the detection of increased levels of MN in urothelial cells can be a useful approach to detect individuals prone to have bladder cancer, and/or to assess the prognosis of the pathology. Increased MN frequencies in urothelial cells of humans populations have been associated to those risk factors involved in bladder cancer such as tobacco (Zamani et al, ), arsenic (Paul et al, ), and occupational exposure to organic solvents (Hoyos‐Giraldo et al, ). Additionally, MN formation was detected in the bladder cells of rats exposed to orto‐phenylphenol, a fungicide and antibacterial agent well known as a bladder tumor inducer in rats (Balakrishnan and Eastmod, ).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of MN within these cells are associated with genetic defects in genome maintenance, exposure to genotoxic agents, accelerated aging, oral cancer risk, and neurodegenerative diseases. [ 12 ] MN is considered as small detached portion of extranuclear DNA which is formed during cell division. This serves as a marker of DNA damage and hence used to determine the cellular damage caused by genotoxic agents.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of smoking on the presence of MN and NA in buccal mucosa cells has been a controversial topic, because some authors have found no relationship, whereas others found an association [10,55,[56][57][58][59][60][61][62]. Some authors have considered diet and the number and type of cigarettes smoked per day (packs per year, with or without filters, regular or light, type and origin of snuff) [55,61,63], but results have been variable.…”
Section: Smokingmentioning
confidence: 99%